Answer:
F(x)=-x^2-4x-1
Step-by-step explanation:
According to PEMDAS, do the exponent part for the parentheses, sense it goes first.
F(x)= -(x^2+4x+4)+3
Then distribute the - sign
F(x)= -x^2-4x-4+3
Then you simplify
F(x)= -x^2-4x-1
Answer:
-3s + 6
Step-by-step explanation:
Combine like terms. Like terms are terms with the same amount of the same variables. In this case:
8s - 11s + 6
(8s - 11s) + 6
-3s + 6
-3s + 6 is your answer.
~
-4.5 if you were to graph the linear function.
Answer:
distributive property
Step-by-step explanation:
-5x+10
multiply everything in the parenthesis by -5
Hey there!!
Equations given :
y = x² - x - 20 -------- ( 1 )
y = 3x - 15 ------------ ( 2 )
Now, lets first solve for the 1st equation ...
... x² - x - 20
We can write -x as -5x + 4x
... x² + 4x - 5x - 20
... x ( x + 4 ) - 5 ( x + 4 )
... ( x - 5 ) ( x + 4 )
y = ( x - 5 ) ( x - 4 )
Now, let's solve the second equation ...
y = 3x - 15
... y = 3 ( x - 5 )
We have two equations, now getting them together..
3 ( x - 5 ) = ( x - 5 ) ( x - 4 )
Divide by x-5 on both sides
3 = x - 4
Add 4 on both sides
x = 7
The value of x is 7
Now substituting this, we get the value of y
We have,
y = 3x - 15
... y = 3(7 ) - 15
... y = 21 - 15
... y = 6
Hence, the ordered pair is ( 7 , 6 )
Hope my answer helps!